The Myth of the Great Patriotic War in Post-Communist Russian Cinema: Causes, Effects, Perspectives - Ilya Tsibets (Review (Institute of National Remembrance), 2021)
This article is an original attempt to define the main features of the myth of the Great Patriotic War in post-Communist Russian cinema. By combining historical, cultural and film studies, the author defines the reasons for the appearance of the above-mentioned myth and its popularity, and indicates the effects of the ideologisation of an event which has been important for politics of history during the rule of Boris Yeltsin and Vladimir Putin. The article will cite examples of films containing repetitive narrative elements that appear with varying intensity and regularity in the Russian political and public discourse on the Great Patriotic War. The author will also refer to how such films have been received, and will define a potential perspective for the further development of this theme.